Potensi Serapan Gas Karbondioksida (CO2) Pada Jenis-Jenis Pohon Pelindung Jalan - Mansur, Muhammad; Pratama, Bayu Arief (Perhimpunan Biologi Indonesia, 2014)
A Study of Potential Absorption of Carbon Dioxide (CO2) in Wayside Trees in Bogor City around was conductedin April to May 2013 by using a portable LCi ADC Bioscientific Ltd. Photosynthesis System. Inventory of waysidetrees species in the site was done by surveys, and sixty-three samples from twenty-one species of wayside trees havebeen measured. This study for determined the ability of CO2 absorption in each species of wayside trees species.Twenty one species of wayside trees were recorded. Angsana (Pterocarpus indicus), Mahogany (Swieteniamacrophylla), Walnuts (Canarium indicum), and Tanjung (Mimusops elengii) were common wayside trees planted inBogor and surrounding areas. The highest rate of CO2 absorption was recorded for Kersen (Muntingia calabura) onaverage of 23.92 ÃÂ¼mol/m2/s , followed by the Bintaro (Cerbera manghas) 16.42 ÃÂ¼mol/m2/s, Dadap (Erythrina cristagalli)16.38 ÃÂ¼mol/m2/s, and Trembesi (Albizia saman) 15.87 ÃÂ¼mol/m2/s. A common planted species in the rangebetween 8 to 13 ÃÂ¼mol/m2/s, such as; Angsana (Pterocarpus indicus) 12,79 ÃÂ¼mol/m2/s, Walnuts (Canariumindicum) 9,39 ÃÂ¼mol/m2/s, Tanjung (Mimusops elengi) 8,72 ÃÂ¼mol/m2/s and Mahogany (Swietenia macrophylla) 8,30ÃÂ¼mol/m2/s. While the lowest CO2 absorption is Burahol (Stelechocarpus burahol) 7.16 ÃÂ¼mol/m2/s, BungaSaputangan (Maniltoa grandiflora) 7.89 ÃÂ¼mol/m2/s and Damar (Agathis alba) 7.86 ÃÂ¼mol/m2/s. There were positivecorrelation between transpiration rate with CO2 absorption rate and stomatal conductance on all the tree specieswere measured.Keywords: CO2 absorption, wayside trees, Bogor.